2009
DOI: 10.1097/dbp.0b013e3181a7ed42
|View full text |Cite
|
Sign up to set email alerts
|

Physician Behavior in the Care of Pediatric Chronic Illness: Association With Health Outcomes and Treatment Adherence

Abstract: Future research should be guided by a comprehensive model of physician behavior in chronic illness management that considers contextual determinants (e.g., culture and socioeconomic status), identifies clinically relevant targets for intervention, and documents the impact on health outcomes. Approaches to chronic illness management that involve physicians in active communication, support, and decision making with children with chronic illness and their parents should be developed and evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 56 publications
3
62
0
4
Order By: Relevance
“…Interventions that improve communication between providers and families will be critical. 6,7 Fourth, health care providers often already monitor patient' s medical information related to adherence and health outcomes (eg, for patients who have type 1 diabetes, HbA1c), and thus can provide patients with real-time feedback on the consequences of their adherence. Consensus statements for the management of certain pediatric illnesses (eg, asthma), in fact, encourage health care providers to provide adherence or self-management support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions that improve communication between providers and families will be critical. 6,7 Fourth, health care providers often already monitor patient' s medical information related to adherence and health outcomes (eg, for patients who have type 1 diabetes, HbA1c), and thus can provide patients with real-time feedback on the consequences of their adherence. Consensus statements for the management of certain pediatric illnesses (eg, asthma), in fact, encourage health care providers to provide adherence or self-management support.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there have been calls for pediatric health care providers to provide adherence promotion interventions. 6,7 However, there have been no systematic reviews or meta-analyses of pediatric health care provider-delivered adherence promotion interventions. Such a review could serve as a foundation for development and dissemination of interventions, particularly in the current environment of health care reform.…”
mentioning
confidence: 99%
“…Исследования продемонстрировали, что именно совместное принятие решений связано с более высокой приверженностью и улучшением достигну-тых результатов лечения как у взрослых, так и у детей [43,44]. Показано, что обучение специалистов такому ориентированному на пациента подходу помогает повы-сить контроль над астмой у детей [14,45,46]. Необходимо отметить, что отсутствие контроля над астмой у пациентов детского возраста может быть обусловлено несоблюдением принципов ведения детей с астмой в соответствии с клиническими рекоменда-циями.…”
Section: лекцияunclassified
“…In addition to age, the level of education of the caregiver and child as well as the prognosis, the race and gender of the child appear to be relevant characteristics: pediatricians communicate more and better with white and female children, with parents and children with higher educational levels and also with children with better prognosis regarding treatment (Drotar 2009;Gabarra and Crepaldi 2011;Stivers 2011Stivers , 2012Stivers and Majid 2007;Taylor et al 2010;Zwaanswijk et al 2011). Conversely, studies from Fiks et al (2010) and Wissow et al, (2005) showed no associations between communicative patterns and sociodemographic data of parents and children.…”
mentioning
confidence: 99%
“…The literature has focused on communication in pediatric settings in the last three decades due to the fact that this process is strongly related to quality of life, treatment adherence, symptom management, satisfaction with health service, fewer outpatient returns and better coping with treatment related difficulties (Ammentorp et al 2011;Coyne and Gallagher 2011;Croom et al 2011;Drotar 2009;Sleath et al 2012).…”
mentioning
confidence: 99%